Investigation of Social Impact Levels of Students Studying at the Faculty of Sport Sciences - MERGAN, Barış; YAZICI, Ömer Faruk; KARGÜN, Mehmet (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2022)
Social influence is regarded as an external factor that has an impact on people’s lives. Individuals’ quality of life can be influenced by social activities such as organizations, events, and activities. Because social influence can affect societies through a variety of activities, it can be one of the research topics in various disciplines. Individuals in society are affected directly or indirectly by sports activities. In this regard, sports may be considered to have a social impact. Sports’ impact on the physical and mental health of individuals in societies may indicate that sports have a social impact. In this context, the study intends to investigate the social impact levels of the faculty of sports sciences students. The descriptive survey model, one of the quantitative research methods, was used to design the study. The "Easily Available Sampling" method was used to select the study group, and 287 students took part in the study. The ’social impact’ scale was used as the data collection tool in the study. The data obtained from the participants were submitted to the statistical process using the IBM SPSS 25.0 package program. According to analyzed results, there was no statistically significant difference between the total mean scores of the social impact scale and the variables of gender, active sports status and department. Social impact scores of students doing active sports were found to be higher than those who do not. The total mean score obtained from the social impact scale of the students studying in Physical Education and Sports Teaching was found to be higher than the students in Sports Management and Coaching Education. The mean total score obtained by male students from the social impact scale was found to be higher than female students.